2016
DOI: 10.1093/mnras/stw636
|View full text |Cite
|
Sign up to set email alerts
|

A search for water masers associated with class II methanol masers – II. Longitude range 341° to 6°

Abstract: This is the second paper in a series of catalogues of 22-GHz water maser observations towards the 6.7-GHz methanol masers from the Methanol Multibeam (MMB) Survey. In this paper we present our water maser observations made with the Australia Telescope Compact Array towards the masers from the MMB survey between l = 341 • through the Galactic centre to l = 6 • . Of the 204 6.7-GHz methanol masers in this longitude range we found 101 to have associated water maser emission (∼ 50 per cent). We found no difference… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 76 publications
4
48
1
Order By: Relevance
“…The fraction of solitary methanol maser sites is higher than solitary OH maser sites (21%) and solitary water maser sites (39%). A sensitive 22 GHz water maser survey toward the MMB masers found that ∼48% of 6.7 GHz methanol masers have a 22 GHz water maser counterpart (Titmarsh et al 2014(Titmarsh et al , 2016, which is higher than our result (38/112, 34%). Moreover, Breen et al (2010b) made a targeted search for 22 GHz water masers toward star formation OH maser sites and concluded about 79% of OH masers sites show coincident water maser emission.…”
Section: Star Formation Sitescontrasting
confidence: 94%
“…The fraction of solitary methanol maser sites is higher than solitary OH maser sites (21%) and solitary water maser sites (39%). A sensitive 22 GHz water maser survey toward the MMB masers found that ∼48% of 6.7 GHz methanol masers have a 22 GHz water maser counterpart (Titmarsh et al 2014(Titmarsh et al , 2016, which is higher than our result (38/112, 34%). Moreover, Breen et al (2010b) made a targeted search for 22 GHz water masers toward star formation OH maser sites and concluded about 79% of OH masers sites show coincident water maser emission.…”
Section: Star Formation Sitescontrasting
confidence: 94%
“…through outflows) than the 6.7-and 12.2-GHz masers that are more directly related to the evolution of the protostar. Recently, Titmarsh et al (2016) compared the occurrence of 6.7-and 12.2-GHz methanol masers and water masers in the 341 • -6 • longitude range and arrived at a similar conclusion.…”
Section: Discussionmentioning
confidence: 70%
“…Across the full MMB range, the median velocity of 6.7-GHz methanol masers is 6 km s −1 (Green et al 2017) and the median of 12.2-GHz sources is 1.7 km s −1 and therefore are consistent with the sub-sample we consider here. The fact that the water masers show the largest velocity range is expected, particularly because of their tendency to trace high-velocity outflow, but the median velocity of the HOPS sources is significantly lower than either of the Breen et al (2010b) or Titmarsh et al (2014Titmarsh et al ( , 2016 targeted water maser observations which have medians of 15 and 17 km s −1 , respectively. A part of this difference can be accounted for by the fact that the Walsh et al (2014) quoted peak velocities of spots and therefore results in an underestimation of the velocity ranges of sites, but some of the difference is due to the unbiased nature of HOPS.…”
Section: Basic Properties Of the Different Maser Populationsmentioning
confidence: 88%
“…The consistency with the Titmarsh et al (2016) sample is probably reflective of the fact that they also use a portion of the complete sample of MMB masers, but it is interesting that the percentage of sources remains constant with the much more sensitive Titmarsh et al (2016) sample, suggesting that the distribution holds to lower water maser peak flux densities.…”
Section: Comparing Methanol Maser Velocities To Water and Excited-stamentioning
confidence: 96%